How to do relevant research : from the ivory tower to the real world - Mirvis, Philip H.; Mohrman, Susan Albers; Worley, Christopher G. (Edward Elgar Publishing, 2021)
"Amidst rapid and fundamental shifts in the economic, geo-political, technological, and societal landscape, this cutting-edge book makes the timeless case that research can be informed by problems in the 'real world' and make important contributions to theory and practice. Throughout the book, the authors argue that there is a 'sweet spot' where both scholarly and practical research can be done simultaneously. It offers readers insightful and rich examples of how this can be achieved, including frameworks, examples, ideas, and tools which will guide researchers in the lifelong task of defining themselves as researchers and crafting their own unique research practice. It also features critical insights into careers oriented toward having impact on practice, reflective questions that make the principles personal and relevant, and a framework to help develop the network of connections required for research to impact practice. Speaking to the graduate student in all of us, How to Do Relevant Research will greatly benefit Ph.D. students and early career academics who gravitate towards this kind of research but worry about its feasibility and instrumentality, mid-to-late career scholars who do research for practice and teach young scholars how to do it, and to researchers in a think-tank or consultancy who want their work to be scientifically sound and practically useful"--